Missing risk sharing markets and the benefits of cross hedging in developing countries - Udo Broll; Jack E. Wahl (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
We study the impact of exchange rate risk on an exporting firm in a developing country when there is no forward market in the foreign currency. However there exists a forward traded asset in this country the price of which is highly correlated to the foreign currency. By indirectly hedging its foreign exchange exposure the firm can increase its economic welfare. Furthermore export production increases and promotes international trade of the developing country if the spot rate of foreign exchange has a regression relationship with the price of the forward traded asset.
Keywords: O12; O16; 330; missing markets; export production; exchange rate risk; cross hedging; wealth risk; Multinationales Unternehmen; Währungsmanagement; Warenbörse; Hedging; Theorie; Entwicklungsländer